Tareas comunicativas en la enseñanza de segunda lengua - Lozada Trimbath, Minnie E. (2007)
Innovations can present difficulties for teachers who are new to their use. In second language teaching, this is often the case when trying to implement a communicative approach and methodology. The author attempts some clarifications on the background of this approach, and focuses on one of its teaching strategies, the so-called communicative task.